Cardiac and vascular toxicities of angiogenesis inhibitors: The other side of the coin. Issue 2 (November 2015) - Alameddine, Raafat S.; Yakan, Ahmad Sharif; Skouri, Hadi; Mukherji, Deborah; Temraz, Sally; Shamseddine, Ali
Highlights Inhibition of vascular endothelial growth factor (VEGF) alters endothelial homeostasis, and causes hypertension, thrombosis and bleeding, but can also delay neointima formation. The presence of off-targets associated with multi-targeted tyrosine kinase inhibitors accounts for their increased cardiac toxicity. Several meta-analyses have reported an increased risk of congestive heart failure, left ventricular dysfunction and coronary arterial events with angiogenesis inhibitors. A novel strategy should include a comprehensive battery of clinical, laboratory and echocardiographic parameters to better delineate the magnitude of these adverse effects.